Circular packing for support-free structures - Yanchevskyi, I.; Lachmayer, R.; Mozgova, I.; Lippert, R-B.; Yaskov, G.; Romanova, T.; Litvinchev, I. (EAI Endorsed Transactions on Energy Web, 2020)
An approach for designing topologically optimized parts is proposed. It is used for manufacturing support-free structures by Direct Metal Laser Sintering (DMLS). This integral approach allows obtaining parts taking into account their strength properties. It combines weak sensitivity to the direction of printing with the simplicity of the subsequent post-processing. A circular packing model is proposed to optimize the part geometry subject to the DMLS constraints. A fast heuristic algorithm is developed to solve the corresponding optimization problem. A prototype obtained by this optimized design approach is presented.